If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20d + 12 + -12d = -43 Reorder the terms: 12 + 20d + -12d = -43 Combine like terms: 20d + -12d = 8d 12 + 8d = -43 Solving 12 + 8d = -43 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 8d = -43 + -12 Combine like terms: 12 + -12 = 0 0 + 8d = -43 + -12 8d = -43 + -12 Combine like terms: -43 + -12 = -55 8d = -55 Divide each side by '8'. d = -6.875 Simplifying d = -6.875
| 1/4=-1/85/4X | | 6k^2+13k-5a^2=0 | | 22=-11r | | 1/16=-x/11 | | -3+p=7 | | 4/11-6 | | -3+p= | | 4/5x-6=5 | | 6*5+4*10=10c | | (5/2)t-t=3+(3/2)t | | (-2/3)t-3=-5 | | 7x+4=7(x+2) | | n+n+2+n+4=126 | | 36x^2-75m^2=0 | | 3p/5+10=16 | | 4(x+4)/3=3x-2 | | y=-7.36(315)-14354.33 | | 3*1+n=45 | | -10=2-4*n | | (-2/5)5+3=1 | | 230w+0.25m=470.00 | | 0.20x+0.45(50)=26.5 | | Y=1700+0.6Y | | 174-5x=40x+24 | | (n-2/3)=3 | | X/5+15=0 | | -2(y-5y)+9=-6(2y-y)+3+13y | | (16x*-12x+2)/(4x-2) | | 2(x-2)6(2-8x)+5= | | -n/5=-2 | | -2(y-5y)+9=-6(2y-y)+3+3y | | 5(5+n)=55 |